Case Report: Virtual natural environment solution helped a child cope with a painful procedure - Karppa, Elina; Puura, Kaija; Jyskä, Ilmari; Turunen, Markku; Palmu, Sauli (Frontiers in Pediatrics, 2024)
Fear of needles is a common phenomenon that can affect the patient's ability to function and to seek medical help. Novel treatment practices are needed to help children cope with this fear. Based on user feedback, immersive virtual reality applications are effective when distracting the patient during a painful procedure. Better understanding of how virtual reality solutions affect the autonomic nervous system should be acquired.We present the case of a 12-year-old boy attending our study examining a novel virtual reality (VR) relaxation method (VirNE). The clinical study aims to determine if pain and anxiety can be relieved by relaxation that has been induced by a virtual natural environment and guided relaxation exercise-mediated autonomic nervous system stimulation.The patient was able to overcome his fear of needles with the help of the guided relaxation and found significant relief from the distress he was experiencing on his monthly visits to the hospital due to his long-term illness requiring repetitious intravenous cannulations.